2018
DOI: 10.1037/pag0000199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time of day on age-related associative deficits.

Abstract: Time of day is known to influence cognition differently across age groups, with young adults performing better later than earlier in the day and older adults showing the opposite pattern. Thus age-related deficits can be smaller when testing occurs in the morning compared with the afternoon/evening, particularly for tasks requiring executive/controlled/inhibitory processes. Stronger influences of time of day were therefore predicted on associative than on item recognition memory based on their differential req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
(90 reference statements)
3
17
0
Order By: Relevance
“…The response bias measure, c (see Table ), was slightly but significantly more positive for item than for associative memory, P = 0.008, suggesting a greater conservative bias toward responding no/not seen before for item memory. Such a difference has been noted before (Bender, Naveh‐Benjamin, & Raz, ; Maylor & Badham, ). Importantly, there was no effect of condition and no interaction between condition and memory type (both F s < 1), indicating no influence of alcohol on response bias.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The response bias measure, c (see Table ), was slightly but significantly more positive for item than for associative memory, P = 0.008, suggesting a greater conservative bias toward responding no/not seen before for item memory. Such a difference has been noted before (Bender, Naveh‐Benjamin, & Raz, ; Maylor & Badham, ). Importantly, there was no effect of condition and no interaction between condition and memory type (both F s < 1), indicating no influence of alcohol on response bias.…”
Section: Resultssupporting
confidence: 49%
“…First, it was conducted in a naturalistic social setting rather than under distraction‐free laboratory conditions. This may partly account for the slightly lower levels of performance in the no‐alcohol condition in comparison with data from students tested in the evening using a similar paradigm (Maylor & Badham, ), though as already mentioned, the additional prospective memory requirement here may also have contributed to this small difference. (Of course, it could be argued that the present context is more appropriate for applied research.)…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The article by Maylor and Badham (2018) highlights the importance of time of day for associative memory performance. Following on previous studies implicating circadian rhythm, as a moderator of age-related differences in memory (e.g., May, Hasher, & Stoltzfus, 1993), this article shows that older adults' associative memory deficit is the largest when older adults are tested at their nonoptimal times and younger adults are tested at their optimal times. Interestingly, the deficit is minimized when older adults are tested at their optimal times and young adults at their nonoptimal times, and the authors suggest that one potential modulating factor in the effect of time of the day on age-related associative memory deficits is its effect on strategic/elaborative encoding (e.g., Naveh -Benjamin, Brav, & Levy, 2007) and on engaging in recollected processing and strategic retrieval (e.g., Cohn, Emrich, & Moscovitch, 2008), both of which are particularly involved in associative memory performance.…”
Section: Mediators and Predictors Of Associative Memory Declinementioning
confidence: 56%
“…1b) also had the same three fMRI scans on the mornings of days 2, 3, and 5, but they were provided 8 hours TIB sleep on nights 2 to 4. Because previous studies have suggested that time-of-day may modulate brain activity and memory performance [95][96][97][98][99][100][101][102][103][104] , the time of fMRI scans and cognitive tests were fixed for all subjects and kept constant across the whole protocol to minimize the potential confounding time-of-day effects.…”
Section: Methodsmentioning
confidence: 99%